Social change in Central and Eastern Europe: General trends and national patterns - László Csaba (Transformation, Integration and Globalization Economic Research (TIGER), 2006)
The paper addresses five issue areas. First it describes the plurality of trajectories in central and eastern European transformations, offering a broad typology. Then it addresses the drift between acceptance of democracy and the market, owing to growing inequalities. Third, problems of poverty and exclusion are addressed. Fourth, it is addressed if any known model of redistribution emerged in the post-transition economies. Fifth, consequences of the populist turn in European policies are being analyzed. Influences of the EU practices will be dealt with and some preliminary conclusions drawn. These suggest a strong intertwining between social and economic performance that limit theoretically conceivable neoliberal, social democratic, postmodern or conservative - policy choices.
Keywords: 330; Sozialer Wandel; Einkommensverteilung; Armut; Sozialstaat; Osteuropa